1983
DOI: 10.1107/s0021889883010869
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of parameter accuracies in profile analysis of white-beam neutron powder diffraction experiments

Abstract: One of the problems arising in profile analyses of white-beam powder diffraction experiments is that in order to assess the reliability of the refined structure parameters allowance must be made not only for errors in the actual powder data but also for uncertainties in the various wavelength-dependent corrections involved. As a means for such assessments the present work provides a general method in which the incident white neutron flux spectrum is assumed to be measured and combined with the other wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Firstly, the range of accessible d spacings for a given neutron source is greater and, secondly, the analysis is considerably less susceptible to systematic and statistical errors in the instrument calibration. This last point may be rather important since it has recently been suggested that such errors probably outweigh the counting statistics of TOF diffraction patterns (Poyry & Tilli, 1983). When the TOF method is used in conjunction with several diffraction angles, each Bragg peak is convoluted with much of the incident intensity profile such that random irregularities and some systematic errors of this profile lose significance.…”
Section: Comparison With Conventional Diffractometersmentioning
confidence: 99%
“…Firstly, the range of accessible d spacings for a given neutron source is greater and, secondly, the analysis is considerably less susceptible to systematic and statistical errors in the instrument calibration. This last point may be rather important since it has recently been suggested that such errors probably outweigh the counting statistics of TOF diffraction patterns (Poyry & Tilli, 1983). When the TOF method is used in conjunction with several diffraction angles, each Bragg peak is convoluted with much of the incident intensity profile such that random irregularities and some systematic errors of this profile lose significance.…”
Section: Comparison With Conventional Diffractometersmentioning
confidence: 99%